Pengaruh Kurs, Harga, dan PDB terhadap Impor Sapi Australia ke Indonesia - Dona Agus, I Made; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 7, Juli 2016 (pp. 729-947), 2016)
US dollar exchange rate, the price of Australian beef and livestock sector GDP has an important role in the activities of Australian cattle imports to Indonesia. Increased demand for beef on the national market, are not offset by the availability of the number of cattle in Indonesia. To overcome these problems, the government imported cattle from Australia to Indonesia. This study aims to determine the effect of the US dollar exchange rate, the price of Australian beef and livestock sector GDP against imports of Australian cattle to Indonesia. The data used is secondary data and using data analysis techniques multiple linear regression. Based on the results, it can be concluded that the US dollar exchange rate and the price of beef australia significant negative effect on imports of Australian cattle to Indonesia while the farm sector GDP positive and significant effect on imports of Australian cattle to Indonesia.
Keywords: exchange rate, price, gross domestic product, import